2010
DOI: 10.1177/0018726709354131
|View full text |Cite
|
Sign up to set email alerts
|

How satisfied are they and why? A study of job satisfaction, job rewards, gender and temporary agency workers in Australia

Abstract: The temporary agency industry has experienced substantial growth in the past two decades. Although there is research on the quality of Australian agency work, most studies have emphasized economic disparities in outcomes for workers. Representative quantitative research using large-scale Australian data on non-economic outcomes, such as job satisfaction, has been scant. Using a nationally representative sample of Australian workers, I examine the extent to which temporary agency workers are satisfied with thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
104
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(114 citation statements)
references
References 51 publications
5
104
0
5
Order By: Relevance
“…1 1 Other studies refer also to the perceived importance of job attributes, but denote this as work value (Clark, 1996;Kalleberg, 1977), aspiration level or preferences which indicate aspiration levels (Aletraris, 2010;Schokkaert et al, 2011).…”
Section: Determinants Of Job Satisfactionmentioning
confidence: 49%
“…1 1 Other studies refer also to the perceived importance of job attributes, but denote this as work value (Clark, 1996;Kalleberg, 1977), aspiration level or preferences which indicate aspiration levels (Aletraris, 2010;Schokkaert et al, 2011).…”
Section: Determinants Of Job Satisfactionmentioning
confidence: 49%
“…Hierarchical multiple regression analysis was used to test the hypotheses. Following an approach adopted by other researchers (Aletraris, 2010;Bender, Donohue, & Heywood, 2005;Huang & Gamble, 2015), the sample was divided and tested for men and women separately.…”
Section: Methodsmentioning
confidence: 84%
“…Previous research comparing THAs to non-THAs showed that lack of autonomy was one main reason for the lower job satisfaction of agency workers (Aletraris, 2010). Our findings suggest that the lower autonomy and skills utilization of agency workers may be due at least in part to the roles agency workers have in client organizations.…”
Section: Discussionmentioning
confidence: 99%